Enhancing “theory of mind” through behavioral synchrony - Baimel, Adam; Severson, Rachel L.; Baron, Andrew S.; Birch, Susan A. J. (Frontiers in Psychology, 2015)
Theory of mind refers to the abilities underlying the capacity to reason about one's own and others' mental states. This ability is critical for predicting and making sense of the actions of others, is essential for efficient communication, fosters social learning, and provides the foundation for empathic concern for others. Clearly there is incredible value in fostering theory of mind. Unfortunately, despite being the focus of a wealth of research over the last 40 years relatively little is known about specific strategies for fostering perspective taking abilities. We provide a discussion of the rationale for applying one specific strategy for fostering efficient perspective taking—that of engaging in ‘behavioral synchrony’ (i.e. the act of keeping together in time with others). Culturally evolved collective rituals involving synchronous actions have long been held to act as social glue. Specifically, here we present how behavioral synchrony tunes our minds for reasoning about other minds in the process of fostering social coordination and cooperation, and propose that we can apply behavioral synchrony as a tool for enhancing theory of mind.